Nonepitheliotropic lymphoma in a dog: case report - Siepmann, Ellen Cristina; Tanabe, Larissa Yurika; Cestari, Filipe Krasinski; Druziani, Juliana Teixeira; Viott, Aline de Marco (Medicina Veterinária, 2020)
Cutaneous lymphoma is an uncommon neoplasm in dogs and Boxer, Shih Tzu, Cocker Spaniel, Basset Hound and Golden Retriever are predisposed breeds. This report describes the case of a 5-year-old mixed-breed female dog presenting ulcerated and fast-growing skin nodules. Initial cytology revealed a poorly differentiated round cell neoplasm. Excision of nodules was performed due to the emergence of new lesions. Histopathological examination was suggestive of histiocytoma. The lesions recurred after one year, and a surgical excision of nodules was performed. An immunohistochemical examination was carried out to refine the diagnosis, revealing positivity for CD3 markers in neoplastic cells and for HLA-DR in neoplastic lymphoid and reactive histiocytic cells; these findings, coupled with the morphological findings, were compatible with nonepitheliotropic cutaneous T-cell lymphoma. Its etiology has not yet been fully elucidated; however, recurrent skin inflammation may be a predisposing factor, which leads to chronic lymphocytic proliferation. Cutaneous lymphoma (CL) causes nonspecific lesions and its classification as epitheliotropic and nonepitheliotropic (NEL) throughout cutaneous signs is difficult, with NEL being the least described form. Animals affected by this form of lymphoma have lymphadenomegaly, firm and multiple nodules that can extend from the dermis to the subcutaneous layer, alopecic and/or ulcerated, often in chest, head and extremities, with rapid progression, which was compatible with the present case. Definitive diagnosis of CL is obtained through histopathology and immunohistochemistry. The aim is to report a case of nonepitheliotropic cutaneous lymphoma in a dog, with emphasis on its clinical, histopathological, and immunohistochemical aspects.